Comparison of Efficacy of Oral Nifedipine Versus Vaginal Micronized Progesterone in Management of Preterm Labor - Bushra Sultana, Qirat Fatima, Farzana (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Preterm delivery causes the deaths of approximately 1 million children annually. The World Health Organization (WHO) estimates a prevalence of 5–18% of births occur prematurely worldwide; exceptionally rare studies are published comparing nifedipine with progesterone for use in the maintenance of tocolysis. This study compares oral nifedipine to veginal micronized progesterone in preterm labor-prone women Methods: This randomized clinical study was carried out at gynecology department from 02-march 2021 to 01-March-2022. A total of 126 women with pre-term labor ware included. In group A, women took nifedipine 20mg sublingually 3 times every 30 minutes then maintained with nifedipine SR 20mg every 12 hours until 37 weeks of gestational amenorrhea or cervical dilatation >4cm (for 48 hours). In group B, women were asked to take vaginal micronized progesterone tablets of 200mg vaginally once a day or until 37 weeks of gestation amenorrhea or cervical dilatation at >4cm (for 48 hours). We compared premature birth, mode of delivery, side effects, neonate’s respiratory distress, ventilator time, ICU stay, and death rate between the groups. Results: Patients in both groups had similar demographics in terms of age and parity of patients. Pregnancy was delayed with a mean of 19.61±6.66 days in nifedipine group, at the same time the pregnancy was delayed for 33.06±8.66 days in progesterone group (p-value < 0.001). The average birth weight was 2.99 ± 0.29 Kg in nifedipine and 3.20 ± 0.17 Kg in progesterone group (p < 0.001). Conclusion: According to the findings of the present study, Progesterone did not affect overall mortality. Progesterone looks like a promising medicine in this aspect, Keywords: preterm, nifedipine, progesterone, tocolysis